Leveraging Environmental Information Integration to Enable Environmental Management Capability and Performance - Wong, Christina W. Y. (The journal of supply chain management, 2013)
Although environmental sustainability has emerged as an important organizational capability to protect the environment and sustain businesses, there is little knowledge on how it is developed. This is of particular importance when environmental management no longer relies solely on an individual firm's efforts, but on its supply chain partners as well. Building on dynamic capabilities theory, environmental information integration (EII) is defined as the organizational capacity of sharing information on environmental management with supply chain partners to facilitate coordination of environmental management practices. This study examines how EII contributes to environmental management capabilities in terms of corporate environmental innovativeness and adaptability. The research model is empirically tested using data collected from 230 firms. The findings show that supplier EII is insufficient in improving environmental management capabilities. Internal EII contributes to corporate environmental adaptability, while customer EII engenders both corporate environmental innovativeness and adaptability. This study suggests that strategic values of EII go beyond the sharing of environmental management information between supply chain partners, simultaneously contributing to the environmental management capabilities of firms. This study contributes substantially to environmental management research by providing empirical evidence on the specific dimensions of EII in supply chains that contribute to environmental management capabilities and business values.